Research on Gait Planning of Quadruped Robot in Straight and Turning - Dan Wang; Deke Zhou; Jiaqi Yang (Jixie chuandong)
Aiming at the straight and turning movements of quadruped robots， the gait based on the crawling gait is separately planned. The concept of coordinated rotating gait is proposed and used it in in-situ turning. The common point of the foot trajectory of the straight gait and the turning gait on the spot is found， and then this point is used to realize the rapid migration of the gait and use it in the turning motion of the quadruped robot. According to the structure design of the quadruped robot in the early stage， a virtual prototype of a quadruped robot is established. A new evaluation criterion—angle margin criterion （SA criterion） is proposed to evaluate the stability of its planned gait， so as to find the optimal gait. A test platform is set up for testing， and the results showed that the gait planning for straight and turning is reasonable and feasible.